The Brand Loyalty Determinants of Indonesian Local Beauty Product Customers: Is it mediated by Customer Satisfaction and moderated by Brand Trust? - Havidz, Ikramina Larasati Hazrati; Rahmawati, Aprilia Kharen Eka (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this study is to investigate the impact of customer satisfaction mediators and brand trust moderators on brand loyalty among customers of a local beauty product in Indonesia. Researchers wanted to know how to boost customer loyalty to a local beauty product user in Indonesia. This study employed primary data collected via an online survey utilizing a Google form, with respondents chosen using purposive sampling. This study's respondents were women, with a total of 116 respondents aged 18-35 years who utilized a local beauty product in Indonesia. The Structural Equation Model (SEM) was used in this work as a research approach. According to the study's findings, utilitarian value and brand image directly and positively affect consumer satisfaction. Furthermore, brand image and customer satisfaction have a strong direct and positive impact on brand loyalty, and customer satisfaction can buffer the relationship between brand image and brand loyalty. While utilitarian value has no effect on brand loyalty, customer satisfaction cannot mitigate the association between utilitarian value and brand loyalty. Finally, the moderating influence of brand trust cannot affect the link between consumer pleasure and brand loyalty.